Alpha-Klotho Enrichment in Induced Pluripotent Stem Cell Secretome Contributes to Antioxidative Protection in Acute Lung Injury. (25th December 2017) - Gazdhar, Amiq; Ravikumar, Priya; Pastor, Johanne; Heller, Manfred; Ye, Jianfeng; Zhang, Jianning; Moe, Orson W.; Geiser, Thomas; Hsia, Connie C. W.
Abstract : Induced pluripotent stem cells (iPSCs) have been reported to alleviate organ injury, although the mechanisms of action remain unclear and administration of intact cells faces many limitations. We hypothesized that cell-free conditioned media (CM) containing the secretome of iPSCs possess antioxidative constituents that can alleviate pulmonary oxidant stress damage. We derived iPSCs from human dermal fibroblasts and harvested the CM. Addition of iPSC CM to cultured human alveolar type-1 epithelial cells mitigated hyperoxia-induced depletion of endogenous total antioxidant capacity while tracheal instillation of iPSC CM into adult rat lungs enhanced hyperoxia-induced increase in TAC. In both the in vitro and in vivo models, iPSC CM ameliorated oxidative damage to DNA, lipid, and protein, and activated the nuclear factor (erythroid 2)-related factor 2 (Nrf2) network of endogenous antioxidant proteins. Compared with control fibroblast-conditioned or cell-free media, iPSC CM is highly enriched with αKlotho at a concentration up to more than 10-fold of that in normal serum. αKlotho is an essential antioxidative cell maintenance and protective factor and an activator of the Nrf2 network. Immunodepletion of αKlotho reduced iPSC CM-mediated cytoprotection by ∼50%. Thus, the abundant αKlotho content significantly contributes to iPSC-mediated antioxidation and cytoprotection. Results uncover a major mechanism of iPSC action, suggest a fundamental role of αKlotho in iPSC maintenance, and support the translational potential of airway delivery of cell-free iPSC secretome for protection against lung injury. The targeted cell-free secretome-based approach may also be applicable to the amelioration of injury in other organs. Abstract : The secretome of human induced pluripotent stem cells (iPSCs) contains abundant αKlotho, an antioxidative cytoprotective protein, that activates nuclear factor (erythroid 2)-related factor 2-responsive genes, increases total antioxidant capacity, and alleviates oxidative damage in vitro and in vivo. Immunodepletion of αKlotho significantly impairs iPSC secretome-mediated cytoprotection from hyperoxia-induced damage.